Economic impact of rising fertilizer prices on the cereals budget - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
This paper aims to assess the impact on the budget of the main cereal crops in Romania, following the disruptions in the fertilizer market that led to accelerated price increases for this category of inputs. The income and expenditure budgets will be studied, both for the technological framework developed in 2021 and for the one developed in 2022, in the framework of the ADER 23.1.1 project of the Research Institute for Agriculture Economy and Rural Development, and finally the data will be quantitatively analysed, determining the absolute and relative differences related to the main cost elements, as well as the weight of the financial effort made for the application of fertilizers in the different cost structures for the crops: wheat, barley and maize.
Keywords: Q11; Q12; 330; chemical fertilizer price; impact; cereals; Romania; budget